Telecommunication ecosystems: Special features of management and interaction - Alexander A. Kobylko (Ural State University of Economics, 2020)
The article explores the current situation in the telecommunications industry. The current analysis is based on the dual nature of the telecom operator, which can be regarded as an independent ecosystem company and as an infrastructure basis for implementing the model by companies engaged in other areas of the economy. Diversification of services leads to the formation of ecosystems of hightech companies. The methodological framework of the study includes theoretical principles of the ecosystem approach and the theory of management of complex systems. The research methods are deduction, comparison and classification. In the course of the analysis of the telecommunications market, we find that an ecosystem is a complex socio-economic whole consisting of sets of harmoniously functioning blocks. Each ecosystem forms its own industry distinguished from every other. The ecosystem emerges on the basis of the technological platform created by the company. The ecosystem is not built around the company as a legal entity, but precisely around its brand. In order to win the telecom operator’s communication channels, ecosystems interact and unify through partnership or parasitic integration. These integration processes may indirectly indicate that a non-telecommunication company applies the ecosystem concept. The interpenetration of two or more ecosystems can lead to their merger in the future. These particularities show that it is impossible to categorize ecosystem as an unambiguously micro- or mesoeconomic component. Ecosystem management should be based not on the traditional principles of company management, but on a combination of management projects, which are unique, rather than routine, solutions in the form of regulation and assistance in attaining the set goals. The obtained results are of theoretical importance for performing further studies on ecosystem formations in today’s economy. In practical terms, the research results can be useful for the management of companies belonging to various ecosystems to justify the formats of effective business models and development strategies.